Rural-urban transformation, energy consumption, economic growth, and CO2 emissions using STRIPAT model for BRICS countries - Haseeb, Muhammad; Hassan, Sallahuddin; Azam, Muhammad (John Wiley & Sons, Inc., 2016)
The objective of the study is to empirically examine the effects of urbanization, energy consumption, and per capita GDP on CO2 emissions for all member countries from BRICS. Panel data over the period 1990-2014 and the STRIPAT model are used.After panel unit root tests, the method of fully modified Ordinary Least Squares (FMOLS) is applied as an analytical technique.Empirical results reveal that urbanization has a positive and significant relationship with CO2 emissions in all BRICS countries with the exception of Russia. Results also show that GDP per capita in cases of Brazil, Russia, and South Africa will help to mitigate CO2 emissions, while the results are opposite in the cases of India and China. Likewise, energy consumption is positively and significantly causing CO2 emissions in cases of Brazil, India, and China, whereas, it is helping to reduce CO2 emission in Russia, while energy consumption has no impact in the case of South Africa. The findings of the study suggest important policy implications. This study recommends introducing less pollution emission of transport, and constructing long-term and effective system in renewable energy development in order to mitigate side effects of urbanization on the environment. © 2016 American Institute of Chemical Engineers Environ Prog, 36: 523–531, 2017. © 2016 American Institute of Chemical Engineers Environ Prog